RETRACTED: A targeted combination therapy achieves effective pancreatic cancer regression and prevents tumor resistance - Vasiliki Liaki; Sara Barrambana; Myrto Kostopoulou; Carmen G. Lechuga; Elena Zamorano-Dominguez; Domingo Acosta; Lucia Morales-Cacho; Ruth Álvarez; Pian Sun; Blanca Rosas-Perez; Rebeca Barrero; Silvia Jiménez-Parrado; et al. (Proceedings of the National Academy of Sciences, 2025)
Pancreatic ductal adenocarcinoma (PDAC) has one of the lowest cancer survival rates. Recent studies using RAS inhibitors have opened the door to more efficacious therapies, although their beneficial effect is still limited mainly due to the rapid appearance of tumor resistance. Here, we demonstrate that genetic ablation of three independent nodes involved in downstream (RAF1), upstream (EGFR), and orthogonal (STAT3) KRAS signaling pathways leads to complete and permanent regression of orthotopic PDACs induced by KRAS/TP53 mutations. Likewise, a combination of selective inhibitors of KRAS (RMC-6236/daraxonrasib), EGFR family (afatinib), and STAT3 (SD36) induced the complete regression of orthotopic PDAC tumors with no evidence of tumor resistance for over 200 d posttreatment. This combination therapy also led to significant regression of genetically engineered mouse tumors as well as patient-derived tumor xenografts (PDX) in the absence of tumor relapses. Of importance, this combination therapy was well tolerated. In sum, these results should guide the development of new clinical trials that may benefit PDAC patients.